KESANTUNAN OFF RECORD TINDAK DIREKTIF DALAM KALIMAT DEKLARATIF BAHASA JEPANG - Irmayanti, Desy (Paramasastra, 2018)
Pragmatics is the study of meaning which is involved three aspects (triadic) spoken by the speaker or the writer and translated by the listener or the reader. This study aim at analyzing the politeness strategy in the delivery of directive utterances in the dialog of the characters in Japanese drama called Sapuri and Osen. The study which uses the qualitative method, applies documentation method in collecting the data from the dialogue of the characters in Japanese drama called Sapuri and Osen. By using recording method, the form of directive utterances can be determined. Meanwhile, the meaning and politeness strategy of directive utterances are obtained by observation method. The result of the study shows that politeness strategy which is the most spoken in both Japanese Drama (according to the most spoken) is give association clues, give hints, presuppose, use tautologies, under state, use rhetorical questions, overstate, use contradiction, use metaphors, be vague, be incomplete or use ellipsis, be ironic, and over generalize. No data are found for be ambiguous and displace hearer of politeness strategy.